Konstitusi Genetik dan Karakter Fenotipik Galur-galur Padi Pup1 Turunan Varietas Situ Bagendit - Suwaji Handaru Wardoyo; Miftahudin Miftahudin; Sugiono Moeljopawiro; Joko Prasetiyono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Acidity, phosphorus deficiency, and droughtstress are major problems in Indonesia’s Ultisol rice farming.Development of rice lines tolerant to those stresses isexpected to be able to reduce the consumption of Pfertilizer. The objectives of the research were to evaluategenetic constitutive of rice lines (BC2F6 population) derivedfrom Situ Bagendit x Kasalath and Situ Bagendit x NIL-C433crossings, and to evaluate responses of those lines toYoshida nutrient solution under P deficiency and Al stresscondition. The research was conducted at Molecular BiologyLaboratory and Greenhouse of ICABIOGRAD, fromNovember 2011 to May 2013. The result of foregroundanalysis showed that Pup1 locus has been integrated intothe genome of BC2F6 rice lines, eventhough some lines (SK5,SK6, SK7, SK8, SK9, SK10, SK19, and SK20) showedincomplete integration. Background analysis indicated thatmajority (95.7%) of the Situ Bagendit background has beenrecovered in BC2F6 rice lines. Al stress evaluation showed SNlines were more tolerant to P deficiency and Al stress thanthat of SK lines. Pup1 locus showed good expression underlow P and no Al stress. Based on genome proportion andYoshida nutrient solution experiments, a total of three lines,namely SK13, SN2, and SN9, have potential goodcharacteristics. Molecular analysis within a marker-assistedbackcrossing (MAB) experiment should be carried out ateach generation of lines for gaining fully gene segment inadvanced generations.